Telerehabilitation for the Evaluation and Management of a Dizzy Patient: A Mini-Review - Beatrice Milrose V. Rey-Matias; Marvin Louie S. Ignacio; Carl Froilan D. Leochico; Farooq Azam Rathore (Journal of the Pakistan Medical Association, 2025)
Dizziness and vertigo are common, disabling symptoms, especially in older adults. They can negatively affect quality of life and independence of the person. Vestibular rehabilitation is a key treatment, but access is often limited by physical, geographic, and socioeconomic factors. Telerehabilitation has emerged as a viable alternative, particularly during the COVID-19 pandemic. This mini review synthesizes available evidence on vestibular telerehabilitation, focussing on feasibility, delivery methods, outcomes, and future directions. We have included commonly used outcomes measures like balance, gait, gaze stability, dizziness, psychological health, and quality of life. Findings suggest telerehabilitation is an effective alternative to in-person therapy. However, further research is needed to standardize protocols, evaluate cognitive outcomes, and ensure inclusivity across diverse populations. Digital innovations are a promising options for more accessible, patient-centered vestibular care. Keywords: Telerehabilitation; Telehealth; Telemedicine; Vestibular Rehabilitation; Dizziness; Balance